How to Perform English Word Stress on English Pronunciation - Ambalegin Ambalegin; Afriana Afriana (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2023)
Word stress is a suprasegmental feature in English pronunciation. The word stress supports the correct articulation of English pronunciation. This qualitative research revealed the position of stress in English words. This research captured the pattern of English word stress. There are several phonologists discussing the word stress such as Chomsky, Hale, and Giegerich. The data taken was from the Oxford English Dictionary and from the English native spoken by observing, reading, listening, and noting. The way to analyze the data applied the textual analysis. The result of this research is the pattern of the English word stress articulation. From this research, it is known that the number of syllables determines the position of the stress. The ultimate stress occurs in two-syllable words. The penultimate and antepenultimate syllables occur in the words which have more than two syllables. The stress in the first syllable occurs in one-syllable, two-syllable, three-syllable, and four-syllable words. Stress does not fall on the affixes. However, the stress falls on the preposition for phrasal verbs. There is variation of stress position on the compound nouns and noun phrases due to their formation. Knowing stress’ position while pronouncing English helps distinguish the meaning literally.